The stable archipelago in the region of the Pallas and Hansa dynamical families - Carruba, V. [UNESP] (Wiley-Blackwell, 2010)
Among highly inclined asteroids, the region of the central main belt between the 3J:-1A and 5J:-2A mean-motion resonances has long been known to host the Pallas and Hansa dynamical families. This region is characterized by the presence of the nu(6), nu(5) and nu(16) secular resonances, which in conjunction with the 8J:-3A mean-motion resonance divide the area into eight regions, the stable islands of the archipelago. Using a set of proper elements available at the Asteroids Dynamic Site (AstDyS) at the time, Gil-Hutton identified a family around (686) Gersuind and two more minor clumps around (945) Barcelona and (148) Gallia in the space of synthetic proper elements. In this work I compute a new set of synthetic proper elements for 2310 numbered and 2142 multi-opposition objects in this region. The use of the frequency-modified Fourier transform method allowed me to obtain non-negative estimates of the proper frequency of argument of pericentre precession g for members of the Hansa families characterized by values of e(forced) larger than e(free), and to solve the problem of the non-linear dependence of g versus n observed by Carruba & Michtchenko.My analysis shows that the two minor clumps of Gil-Hutton should now be considered dynamical families. Also, a new family in the domains of both proper elements (a, e, sin i) and frequencies (n, g, g + s) around (1222) Tina is discovered in this work, as well as a new frequency family around (4203) Brucato. Nine minor clumps, one of which is visible in both domains, are also observed.The taxonomical analysis of family members suggests that the Pallas family is compatible with a B-type composition (but two members are classified as C interlopers), while the Hansa family is possibly an S-type one. Sloan Digital Sky Survey Moving Object Catalog (SDSS-MOC3) data suggest that the Barcelona family might be an Sq group, and the Gersuind, Gallia and Tina ones should belong to the S complex. Geometric albedo data seem to confirm the possibility that the Barcelona and Gersuind families belong to the S complex. Data on cumulative size distributions, collisions time-scales, rotation rates and dynamics in this region are also revised in this work.
Keywords: celestial mechanics; minor planets, asteroids: general